Persistent distention of colon damages interstitial cells of Cajal through Ca2+‐ERK‐AP‐1‐miR‐34c‐SCF deregulation. Issue 9 (4th June 2017) - Yang, Shu; Dong, Fang; Li, Dandan; Sun, Haimei; Wu, Bo; Sun, Tingyi; Wang, Yaxi; Shen, Ping; Ji, Fengqing; Zhou, Deshan
Abstract: Gastrointestinal motility disorders (GMDs) are attributed to loss of interstitial cells of Cajal (ICC), whose survival and function are deeply dependent on the activation of KIT/SCF signalling. Based on the facts that gastrointestinal distention is common in GMD patients and SCF produced by smooth muscle cells (SMCs) is usually decreased before ICC loss, we considered a possible contribution of persistent gastrointestinal distention/stretch to SCF deficiency. In this study, chronic colonic distention mouse model, diabetic gastrointestinal paresis mouse model, cultured mouse colonic SMCs and colon specimens from Hirschsprung's disease patients were used. The results showed that SCF was clearly decreased in distent colon of mice and patients, and microRNA array and real‐time PCR indicated a concomitant increase of miR‐34c in distent colon. A negative regulation of miR‐34c on SCF expression was confirmed by luciferase reporter assays together with knock‐down and overexpression of miR‐34c in cultured colonic SMCs. Using EMSA and ChIP assays, we further consolidated that in response to persistent stretch, the transcription factor AP‐1/c‐Jun was highly activated in colonic SMCs and significantly promoted miR‐34c transcription by binding to miR‐34c promoter. Knock‐down or overexpression of AP‐1/c‐Jun in cultured colonic SMCs leads to down‐ or up‐regulation of miR‐34c, respectively. In addition, the activation of AP‐1/c‐Jun was through ERK1/2 signalling provoked by Ca 2+ overload in colonic SMCs that were subject to persistent stretch. In conclusion, our data demonstrated that persistent distention/stretch on colonic SMCs could suppress SCF production probably through Ca 2+ ‐ERK‐AP‐1‐ miR‐34c deregulation, resulting in ICC loss or impairment and GMD progress.